2021
DOI: 10.1038/s41598-021-03244-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of renin–angiotensin–aldosterone system inhibitors on organ-specific ace2 expression in zebrafish and its implications for COVID-19

Abstract: Among cases of SARS-CoV-2 infections that result in serious conditions or death, many have pre-existing conditions such as hypertension and are on renin–angiotensin–aldosterone system (RAAS) inhibitors. The angiotensin-converting-enzyme-2 (ACE2), a key protein of the RAAS pathway, also mediates cellular entry of SARS-CoV-2. RAAS inhibitors might affect the expression levels of ace2, which could impact patient susceptibility to SARS-CoV-2. However, multi-organ-specific information is currently lacking and no sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The relationship between the use of ACEI and the incidence and severity of COVID-19 should be investigated in further studies, especially in vaccinated HD patients. Determination of ACE2 expression could help confirm such a relationship and our hypothesis [46].…”
Section: Discussionsupporting
confidence: 61%
“…The relationship between the use of ACEI and the incidence and severity of COVID-19 should be investigated in further studies, especially in vaccinated HD patients. Determination of ACE2 expression could help confirm such a relationship and our hypothesis [46].…”
Section: Discussionsupporting
confidence: 61%
“…Vertebrate models of zebrafish indicate that RAASi exposure increases expression of ACE2, highlighting the possible interrelationship between RAASi, ACE2 and COVID-19. 29 While reassuring that the use of guideline directed cardiovascular therapies did not decrease during the COVID-19 pandemic, 30 the specific role of RAASi in the context of COVID-19 infections have been explored observational studies 31 , 32 and randomized control trials. 12 , 13 These studies have collectively shown no increase in the risk for COVID-19 severity in patients who continued compared to those who discontinued RAASi therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our decision to concentrate on the anterior regions of developing embryos/larvae was due to the early appearance of the anterior peripheral sense organs ( 41 , 62 ) and their associated brain regions at these early stages ( 84 ), thus limiting the possible sites of viral entry. Our approach was to identify tissues/organs that express the ACE2 receptor ( 2 , 3 , 74 ) and then link this with the expression of TPC2, reported to be required for vesicle trafficking during SARS-CoV-2 infection ( 17 19 ), and associated endocytic activity, a proposed mechanism and pathway of host cell entry ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the nascent status of the olfactory organs at ~5 dpf, we propose that due to a similar combination of factors (i.e., expression of ACE2 and TPC2 and endocytic activity), the sensory cells of the early olfactory epithelium might (like the anterior neuromasts) also be a site of SARS-CoV-2 pseudovirus host cell entry. Other ACE2-expressing tissues and organs have been reported in zebrafish, including the vascular system and the lining of the digestive tract, kidney, liver, gills, and heart ( 3 , 111 , 112 ). However, as the open mouth connects with the pharyngoesophageal region only at 3 dpf ( 64 ), and these link with the rest of digestive tract (and associated organs) to form a continuous structure only at 5 dpf ( 69 ), we suggest that initially, the anterior sensory organs represent the major sites of ACE2-mediated host cell entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation